Does Motivation Lead to Organizational Citizenship Behavior? a A Theoritical Review (Global Journal of Management and Business Research, 2016)
The theories of organizational citizenship behavior have been an area of interest of many scholars for decades. However, very little work has been done in this area to see if motives of various kinds lead to organizational citizenship behavior. This paper discusses definition of motivation and few popular theories of motivation. A thorough literature review is done to learn aspects of organizational citizenship behavior and its relationship with motivational concepts. It is found that both extrinsic and intrinsic motivation affects employee's commitment to organizational citizenship behavior. Factors like trust, leadership style, and changed attitude towards employees can increase OCB at workplace which will increase their performance and reduce turnover rate. The major limitation of the paper is that it is based on very limited number of scholarly reviews as little work has been done in this field. There is huge scope for potential researchers to conduct this research with primary data, across different culture and different industries which would give a complete understanding of the subject matter.
Keywords: extrinsic; intrinsic; employee performance; organizational citizenship behavior; motivation